The Cold War and Western Perspectives on Soviet Science - Climério Paulo da Silva Neto (Revista Brasileira de História da Ciência, 2016)
This essay presents an overview of the dominant trends in the Western historiography on the Soviet Union along the Cold War inquiring how they affected the perspectives on the history of Soviet science. It discuss three major trends, namely totalitarian school, which resonated with Robert Merton and Karl Popper’s claims that science best develops in democratic societies; the revisionists, which came of age in the 1960s and resembled some schools of the sociology of science both in their motivation to subvert the dominant perspective in their discipline and in their methodological choices; and, finally, the post-Cold War and post-revisionists perspectives on Soviet history and history of Soviet science, and how they challenged widely held beliefs on Soviet science and society that underpinned many Cold War-era works on the Soviet Union. The conclusion discussed how the historiography of Soviet Science resonates with Christopher Hill’s claim that history needs to be rewritten at every generation.